Development of Digital Module "Oral History Documentation of South Tapanuli People's Struggle During the PRRI Period: Mentoring Assistance for MA Students at Musthafawiyah Pesantren Purba Baru in Interview Techniques and Narrative Analysis" - Burhanuddin, Burhanuddin; Nasution, Bincar (International Journal of Community Service (IJCS), 2025)
This qualitative research investigates the development and implementation of a digital module designed to facilitate oral history documentation regarding the Revolutionary Government of the Republic of Indonesia (PRRI) struggle within South Tapanuli communities. The study focuses on mentoring assistance provided to Madrasah Aliyah (MA) students at Pondok Pesantren Musthafawiyah Purba Baru, emphasizing the acquisition of interview techniques and narrative analysis competencies. This research employed a qualitative methodology encompassing semi-structured interviews, classroom observations, and participant documentation analysis conducted over six months with 28 MA students and 5 faculty mentors. Through iterative coding and thematic analysis, three core emergent themes were identified: (1) scaffolded skill development in oral history methodology, (2) students' evolving understanding of historical agency and community memory preservation, and (3) institutional integration challenges within pesantren educational frameworks. The digital module demonstrated significant effectiveness in enhancing students' interview competencies, with 89.3% of participants demonstrating advanced capability in conducting biographical narrative interviews by the research conclusion. Findings revealed that mentoring relationships characterized by reciprocal feedback mechanisms and culturally responsive pedagogical approaches substantially facilitated student learning engagement. This research contributes to understanding how digital learning technologies can be meaningfully integrated within Islamic boarding school contexts to foster students' historical consciousness and community documentation skills while preserving traditional pedagogical values.